Lockdown : a novel of suspense - King, Laurie R. (Bantam, 2017)
Career Day at Guadalupe Middle School: A day given to innocent hopes and youthful dreams. A day no one in attendance will ever forget. A year ago, Principal Linda McDonald arrived at Guadalupe determined to overturn the schools reputation for truancy, gang violence, and neglect. One of her initiatives is Career Day, bringing together children, teachers, and community presenters in a celebration of the future. But there are some in attendance who reject McDonalds bright vision. A principal with a secret. A husband with a murky past. A cop with too many questions. A kid under pressure to prove himself. A girl struggling to escape a mother's history. A young basketball player with an affection for guns. Even the school janitor has a story he dare not reveal. But no one at the gathering anticipates the shocking turn of events that will transform a day of possibilities into an explosive confrontation. Tense, poignant, and brilliantly paced, Laurie R. King's novel charts compelling characters on a collision course- a chain of interactions that locks together hidden lives, troubling secrets, and the bravest impulses of the human heart.